Dietary Supplementation With Tinospora cordifolia Improves Anxiety-Type Behavior and Cognitive Impairments in Middle-Aged Acyclic Female Rats - Bhandari, Anmol; Sunkaria, Aditya; Kaur, Gurcharan (Frontiers in Aging Neuroscience, 2022)
The midlife transition period in women marks the progressive flattening of neurological health along with increased adiposity, dyslipidemia, frailty, and inflammatory responses which is mainly attributed to the gradual decline in estrogen levels. Conflicting reports of hormone replacement therapy (HRT) necessitate exploration of novel therapeutic interventions using bioactive natural products having the least toxicity and holistic mode of action for the preservation of metabolic homeodynamics with aging in women. The present study was planned to investigate the effects of aging and/or high-fat diet (HFD) on cognitive impairments and anxiety and further their management by dietary supplement with Tinospora cordifolia stem powder (TCP). Acyclic female rats were included in this study as the model system of the perimenopause phase of women along with young 3-4 months old rats as controls. Rats were fed on with and without TCP supplemented normal chow or HFD for 12 weeks. Animals fed on a TCP supplemented normal chow showed consistent management of bodyweight over a 12-weeks regimen although their calorie intake was much higher in comparison to their age-matched controls. Post-regimen, neurobehavioral tests such as Novel Object Recognition and Elevated Plus Maze performed on these animals showed improvement in their learning and memory abilities as well as anxiety-like behavior. Further, due to the presence of multiple components, TCP was observed to modulate the expression of key marker proteins to ameliorate neuroinflammation, and apoptosis, and promote cell survival, and synaptic plasticity in the hippocampus and prefrontal cortex regions of the brain. These findings suggest that TCP supplementation in diet during the mid-life transition period in women may be a potential interventional strategy for the management of menopause-associated anxiety and cognitive impairments and healthy aging.